Hormonal Treatment for Severe Hydronephrosis Caused by Bladder Endometriosis - Erkan Efe; Murat Bakacak; Salih Serin; Eyüp Kolus; Önder Ercan; Sefa Resim (Case Reports in Urology)
The incidence of endometriosis cases involving the urinary system has recently increased, and the bladder is a specific zone where endometriosis is most commonly seen in the urinary system. In the case presented here, a patient presented to the emergency department with the complaint of side pain and was examined and diagnosed with severe hydronephrosis and bladder endometriosis was determined in the etiology. After the patient was pathologically diagnosed, Levonorgestrel-Releasing Intrauterine System (LNG-IUS) was administered to the uterine cavity. At the 12-month follow-up, endometriosis was not observed in the cystoscopy and symptoms had completely regressed. Hydronephrosis may be observed after exposure of the ureter, and silent renal function loss may develop in patients suffering from endometriosis with bladder involvement. For patients with moderate or severe hydronephrosis associated with bladder endometriosis, LNG-IUS application may be separately and successfully used after conservative surgery.